Evolutionary Mismatch in Mating - Goetz, Cari D.; Pillsworth, Elizabeth G.; Buss, David M.; Conroy-Beam, Daniel (Frontiers in Psychology, 2019)
Evolutionary mismatch concepts are being fruitfully employed in a number of research domains, including medicine, health, and human cognition and behavior to generate novel hypotheses and better understand existing findings. We contend that research on human mating will benefit from explicitly addressing both the evolutionary mismatch of the people we study and the evolutionary mismatch of people conducting the research. We identified nine mismatch characteristics important to the study of human mating and reviewed the literature related to each of these characteristics. Many of the people we study are: exposed to social media, in temporary relationships, relocatable, autonomous in their mating decisions, nulliparous, in groups that are socially segmented, in an educational setting, confronted with lots of options, and young. We applied mismatch concepts to each characteristic to illustrate the importance of incorporating mismatch into this research area. Our aim in this paper is not to identify all potential mismatch effects in mating research, nor to challenge or disqualify existing data. Rather, we demonstrate principled ways of thinking about evolutionary mismatch in order to propel progress in mating research. We show how attending to the potential effects of mismatch can help us refine our theoretical and methodological approaches and deepen our understanding of existing patterns in the empirical record. We conclude with specific recommendations about how to include consideration of evolutionary mismatch into research on human mating.